PEMANFAATAN SMARTPHONE SEBAGAI MEDIA PEMBELAJARAN GEOGRAFI SISWA KELAS XI IPS DI SMA NEGERI 13 PADANG - Amalia, Miftahul Nur; Rahmanelli, Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The purpose of this research is to describe things as follows. (1) the use of smartphones as a medium for learning geography. (2) constraints in the use of smartphones as geography learning media. (3) efforts to overcome obstacles in using smartphones as a medium for learning geography for class XI IPS students at SMA Negeri 13 Padang. The method used in this research is interview method with qualitative research. The subject of this study was class XI IPS 5. The data source for this research was the results of interviews with teachers and students. Data collection techniques are observation, interview, and documentation techniques. Data analysis techniques are data reduction, data presentation, and conclusions. The results of this study indicate that (1) smartphones make it easier for students to understand geography learning because they get new information, learning videos, and learning materials. (2) the obstacles faced by teachers and students in using smartphones are that the signal is lost, the wifi network is slow, the quota for accessing the internet runs out, the smartphone's memory becomes full because of the large amount of material downloaded, and students misuse smartphones. (3) efforts to overcome obstacles to the use of smartphones as learning media are schools providing computers for students, students restarting smartphones if network disturbances occur or they ask for help who is more knowledgeable. If this is also not resolved, they take turns using smartphones with other friends.